Perdamaian (Dading) sebagai Alternatif Penyelesaian Sengketa Perdata - Supianto Supianto (JURNAL RECHTENS, 2016)
In general peace is a dispute resolution produced by agreement of the parties. The parties are at loggerheads with each other agree to resolve the issue with the word agree to terms. This method is the most appropriate because it is a reflection of the personality of the Indonesian nation, known as the principle of deliberation and kinship. Among the benefits of the settlement of disputes by means of this peace is the voluntary nature of the process, the procedure is quick, non-judicial decision, confidential, flexible, saving time and cost, the maintenance of good relations, more easily controlled and decisions tend to last a long time. The peace efforts must be encouraged and pursued, although the dispute has been included in the examination process of the court.